The Subjunctive Mood in Emmanuel Macron's Presidential Speech - Wibowo, Adisah Fildan; Asnidar, Yusi; Andika, Yunilis (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2025)
This study aims to analyze the meaning of the subjunctive in the speech of French President Emmanuel Macron titled